Teachers practices in handling student offenses at a National High School - Baqued-Qued, Gay C. (City of San Fernando, La Union : [s.n.], 2018)
This descriptive-survey study was designed to analyze the practices of teachers in handling student offenses as basis for a revised student handbook. Specifically, it looked int the offenses committed by the Junior High Students of La Union National High School during the school year 2015-2016 including their most frequent and serious offenses, teacher practices in handling offenses and teacher practices, and limitations that exist in the current student handbook. This study used a content-validated survey questionnaire for teachers and documentary analysis as main tools for data gathering. There were 166 teachers who participated in the study. The data were statistically treated using frequencies and ranking.
Bibliography: pages 106-109.
CHED-La Union
Keywords: Teachers; Secondary Schools